Study on Ankle Movement Model based on Fourier Series - Han Jikai; Luo Yufeng; Shi Zhixin; Xie Dongfu; Liu Zhenkun (Jixie chuandong)
The study of the lower limb movement model of the human body is one of the core contents of the exoskeleton robot driving and control system. Aiming at the shortcomings of complicated fitting process,discontinuity after high order derivation of the model and so on in the fitting process of ankle joint motion model by using piecewise function,the Fourier series method is used to establish the model of the horizontal movement of the ankle joint in the sagittal plane,and the motion model of the ankle joint in the sagittal plane is established by using the polynomial fitting process,it has a simple,accurate,non-impact characteristics by the ankle articulation model obtained by the method,and the model is continuity and the conductivity. Finally,the model can be used to demonstrate the characteristics of the ankle movement in healthy people,at the same time,motion simulation is performed by ADAMAS to verify the correctness of the ankle driver used in exoskeleton robots. The study of the lower limb ankle movement model of the human body provides an important theoretical basis for studying the characteristics of the ankle movement in healthy subjects during normal walking,and provides a reference model for the driving and control of the ankle joint of the exoskeleton.